Assessment of Heavy Metal Contamination in Euphrates River Sediments from Al-Hindiya Barrage to Al-Nasiria City, South Iraq - J.Issa, Murtadha; Qanbar, Alaa Sh. (Iraqi Journal of Science, 2023)
The degree of contamination in the sediments of the Euphrates River (Shatt Al-Hindiya), for the metals As, Cd, Co, Cu, Cr, Mn, Ni, Pb, Sc Se, Sr, V and Zn hasbeen evaluated using the index of geo-accumulation (I-geo), Enrichment factor (EF),Contamination factor (CF) and pollution load index (PLI), whereat the I-geo hasbeen widely utilized as a measure of pollution in freshwater sediment. Enrichmentfactor (EF) is one widely used as approach to characterize the degree ofanthropogenic pollution to establish enrichment ratios, while the pollution loadindex (PLI) represents the number of times by which the heavy metal concentrationsin the sediment exceeds the background concentration, and gives a summativeindication of the overall level of heavy metal toxicity in a particular sample. Byusing these numerical sediments indexes we found that the Sediments of EuphratesRiver in the study area are polluted by the metals of Nickel (maximum 194ppm) andStrontium (maximum 543ppm), and moderately polluted by the metals of Copper(maximum 47.9), Cobalt (maximum 22.8ppm), Chromium (maximum 111ppm) andSelenium (maximum 1.1ppm), while the sediments of Euphrates River are notpolluted by the metals of Arsenic (maximum 10.2ppm), Cadmium (maximum0.29ppm), Manganese (maximum 949ppm), Lead (maximum 14.8ppm), Scandium(maximum 8.96ppm), Vanadium (maximum 81ppm) and Zinc (maximum 91ppm).